'I think he's dead': A cohort study of the impact of caller declarations of death during the emergency call on bystander CPR. (March 2021) - Riou, Marine; Ball, Stephen; Morgan, Alani; Gallant, Sheryl; Perera, Nirukshi; Whiteside, Austin; Bray, Janet; Bailey, Paul; Finn, Judith
Abstract: Background: In emergency calls for out-of-hospital cardiac arrest (OHCA), dispatchers are instrumental in the provision of bystander cardiopulmonary resuscitation (CPR) through the recruitment of the caller. We explored the impact of caller perception of patient viability on initial recognition of OHCA by the dispatcher, rates of bystander CPR and early patient survival outcomes. Methods: We conducted a retrospective cohort study of 422 emergency calls where OHCA was recognised by the dispatcher and resuscitation was attempted by paramedics. We used the call recordings, dispatch data, and electronic patient care records to identify caller statements that the patient was dead, initial versus delayed recognition of OHCA by the dispatcher, caller acceptance to perform CPR, provision of bystander-CPR, prehospital return of spontaneous circulation (ROSC), and ROSC on arrival at the Emergency Department. Results: Initial recognition of OHCA by the dispatcher was more frequent in cases with a declaration of death by the caller than in cases without (92%, 73/79 vs. 66%, 227/343, p < 0.001). Callers who expressed such a view (19% of cases) were more likely to decline CPR (38% vs. 10%, adjusted odds ratio 4.59, 95% confidence interval 2.49–8.52, p < 0.001). Yet, 15% (12/79) of patients described as non-viable by callers achieved ROSC. Conclusion: Caller statements that the patient is dead are helpful for dispatchers to recognise OHCA early, but potentially detrimental when recruiting the caller to perform CPR. There is an opportunity to improve the rate of bystander-CPR and patient outcomes if dispatchers are attentive to caller statements about viability.